Optimization of Extraction Process of Methyl Eugenol and Asarinin in Asarum with Deep Eutectic Solvent Based on the Response Surface Methodology - Huiwei Bao; Yang Xu; Yuejie Wang; Tao Zhang; Enpeng Wang; Xin Huang; Changbao Chen; Fangxin Liu (Journal of Chemistry)
To explore a green and efficient extraction technology for the extraction of active ingredients of Asarum, the deep eutectic solvent combined with ultrasonic was applied to compare the extraction efficiency of 10 kinds of deep eutectic solvents, taking the extraction rate of methyl eugenol and asarinin as indices. Single-factor experiments were adopted to investigate the influence of molar ratio, liquid-to-solid ratio, eddy time, ultrasonic time, and temperature of the deep eutectic solvent on the extraction rate of methyl eugenol and asarinin. Based on single-factor experiments, the surface response methodology was used to optimize the extraction process conditions. The results showed that the optimum extracting process conditions of methyl eugenol and asarinin in Asarum consisted of a ratio of choline chloride to glycerol of 1 : 3, a DES volume of 2 mL, an ultrasonic temperature of 60°C, an ultrasonic time of 30 min, and a vortex oscillation of 7 min. Under the optimum extracting process conditions, the contents of methyl eugenol and asarinin were 1.9428 mg/g and 0.9989 mg/g, respectively, and the comprehensive index was 2.3280 (RSD of 1.91%). The results were close to the predicted values of the response surface model, demonstrating the applicability of the model. The extraction rate of methyl eugenol and asarinin in Asarum by this method was higher than that of water extraction and alcohol extraction, which fully indicated the high efficiency of ultrasonic-assisted green deep eutectic solvent extraction technology. The results provide data support for further development and utilization of Asarum.